Optimized Multiple Unmanned Surface Vehicle Strategies for Target Tracking with Field of View Constraints - Kai Xue; Zeyu Xu; Ping Wang; Qiuhong Li; Zhiqin Huang; Decheng Kong (Journal of Marine Science and Engineering)
Unmanned surface vehicles (USVs) have garnered significant interest due to their potential in various maritime applications, particularly target tracking. However, when USVs perform rotational motion around a target, their operations are often hindered by limited fields of view (FOVs) within formations. In this paper, we establish a constraint propagation model to integrate formation constraints, motion constraints, and FOV constraints. Then, we propose four strategies to enforce FOV constraints. The proposed strategies are divided into two categories: those that adjust formation radius and those that adjust rotational velocity. The advantages and disadvantages of each approach are systematically analyzed, highlighting their suitability for various operational scenarios. The effectiveness and robustness of these strategies are validated through simulations.